Promoting recreational opportunities and experiences of students with disabilities, at a University, in Limpopo Province, South Africa - Mululuma, Anzani; Mugwedi, Ndiafhi Percy; Malema, Makhaya (Frontiers in Sports and Active Living, 2025)
IntroductionThe Limpopo Province is one of the nine provinces in South Africa and has only two universities that serve students with disabilities coming from historically disadvantaged communities. The two universities within the Limpopo Province are categorically classified as Historical Disadvantaged Institutions of higher learning. Therefore, students with disabilities deserve the right to recreational opportunities and experiences while continuing with their tertiary education. A literature review confirmed an existing gap that relates to promoting recreational opportunities and experiences of students with disabilities in universities. The objective of the research was to gain a deeper insight into how recreational opportunities and experiences can be enhanced for students with disabilities at a university in Limpopo Province.MethodsThe study adopted a qualitative research approach using an exploratory design wherein seventeen students with disabilities were purposively selected and consented to participate in the study. The study used semi-structured interviews to collect data.Results and DiscussionThe study findings revealed three main themes, including recreation participation, benefits of active recreation, and more opportunities for participation. This indicates that students with disabilities do not fully participate in recreational activities due to limited accessible recreational activities, conducive facilities, and other societal challenges. The conclusion drawn is that recreational opportunities and experiences of students with disabilities are not adequately promoted in the University. This recommends the need for more exploratory mechanisms to address issues facing students with disabilities holistically.